Des mages à Florence au Quattrocento. Autour de la fête de l’Épiphanie de 1443 - Pauline Duclos-Grenet (Bulletin du Centre d’Études Médiévales d’Auxerre)
The theme of the Magi is among the most popular ones in the imaginary of the Western Middle Ages, and its resonance is absolutely unique. It has been omnipresent in the most various spheres of Christian societies because of its extraordinary symbolic wealth. However, it is in Florence by the late Middle Ages that the production of meaning is the most powerful. The purpose of this essay is to draw the frame of this phenomenon and to understand how it pervades the minds of the period, through the urban rituals and pictural representations which structure the Florentine society. Indeed, ritual processions and pictural representations, in addition to other kinds of discourse, express the will of a republic which dreams of being both a New Jerusalem and a New Rome. Yet above all this significant network, stands the omnipresent figure of Cosimo di Medici as this republican prince chose the Magi as the keystone of his personal and familial ideology discourse. The Epiphany of 1443 is the climax of the process.